CTA Annual Report 2014 - A year in review: Realising the purpose of agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2015)
2014 has been a landmark year for smallholder agriculture and CTA alike. It was the United Nation’s International Year of Family Farming and the African Union’s Year of Agriculture and Food Security. It was also CTA’s 30th anniversary. There were many notable achievements.